2020
DOI: 10.14202/vetworld.2020.2243-2251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Flinders Technology Associates card for transporting bacterial isolates and retrieval of bacterial DNA after various storage conditions

Abstract: Background and Aim: Flinders Technology Associates (FTA) cards simplify sample storage, transport, and extraction by reducing cost and time for diagnosis. This study evaluated the FTA suitability for safe transport and storage of Gram-positive and Gram-negative bacterial cells of animal origin on its liquid culture form and from organ impression smears (tissues) under the same routine condition of microbiological laboratory along with detecting their nucleic acid over different storage conditions. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Diagnostic samples applied to FTA ® cards include cultured microorganisms and infected bodily fluids (e.g., blood, oral fluids, and mucosal secretions). Their use has been validated for a variety of viral and bacterial pathogens ( 24 , 31 , 32 ), and recently, Escherichia coli, Staphylococcus aureus , and Pasteurella multocida have been identified from impression smears of internal organs from chickens collected on FTA ® cards ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic samples applied to FTA ® cards include cultured microorganisms and infected bodily fluids (e.g., blood, oral fluids, and mucosal secretions). Their use has been validated for a variety of viral and bacterial pathogens ( 24 , 31 , 32 ), and recently, Escherichia coli, Staphylococcus aureus , and Pasteurella multocida have been identified from impression smears of internal organs from chickens collected on FTA ® cards ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 10 previous studies have explored fecal collection and storage methods, examining variables such as temperature, storage duration at different temperatures, and the application of stabilizers like the OMNI-gene GUT kit, 95% ethanol, RNAlater, and other preservative solutions (Van der Waaij et al, 1994;Dominianni et al, 2014;Doukhanine et al, 2014;Flores et al, 2015;Loftfield et al, 2016;Song et al, 2016;Vogtmann et al, 2017;Wong et al, 2017;Burz et al, 2019;Conrads and Abdelbary, 2019;Papanicolas et al, 2019;Tap et al, 2019;Wu et al, 2019;Liang et al, 2020;Shalaby et al, 2020). While these studies have identified various methods to achieve stable microbial composition results, a universally accepted standard protocol has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…FTA (Flinders Technology Associates) cards provide important advantages, such as sample storage, transport, and extraction, leading to a decrease in the cost and time needed for molecular diagnosis. FTA cards have been widely used to extract and stabilize DNA from samples of human and swine clinical cases [ 41 , 42 , 43 , 44 , 45 , 46 ]. The method of FTA cards is reported to be a valid diagnostic tool, and it can be used for a short period (24 h) for the storage and transport of live bacteria, specifically Gram-positive types [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…FTA cards have been widely used to extract and stabilize DNA from samples of human and swine clinical cases [ 41 , 42 , 43 , 44 , 45 , 46 ]. The method of FTA cards is reported to be a valid diagnostic tool, and it can be used for a short period (24 h) for the storage and transport of live bacteria, specifically Gram-positive types [ 44 ].…”
Section: Introductionmentioning
confidence: 99%